The Future of The European Union After Britain’s ExitLe Future De L’union Européenne Aprés La Sortie De La Grande Bretagne - Mohamed Safwat, Basant; Touabia, Sara (Finance and Business Economies Review, 2023)
The European Union is the second important geographical, economic, political, and financial grouping after UN in the worldwho has suffered a real earthquake in recent times following the withdrawal of United Kingdom nicknamed by Brexit, knowing that this country is one of the important active members at the scale international, and within NATO.This disastrous event opened all doors for other member countries to follow the same path or way,especially after the appearance and progression of the populist parties of the extreme right such as Austria and Italy who are in the majority in the parliaments and who currently govern their states.The current international political climate favors the weakening of the European Union especially the change recorded in the United States since the election of Donald Trump as the head of the White House,who wants to see Europe economically weak on the one handand so that the EU cannot be compete his country on the other hand.In a way, Europe will not be independent from the United States.